PENGARUH KOMPOSISI MEDIA TANAM DAN KONSENTRASI PUPUK ORGANIK CAIR NASA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN BIT MERAH (Beta vulgaris L.) DENGAN SISTEM POTTING - Efita Febriana; Nora Augustien Kusumaningrum; Makhziah Makhziah (UPN VETERAN JAWA TIMUR, 2020)
Red Beet (Beta vulgaris L.) is one of plant that are benefical to health. The purpose of this study was to determine the composition of the planting media and the concentration of liquid organic fertilizer that is appropriate for increasing growth and production of red beet plants. The study was conducted at the Greenhouse of the Faculty of Agriculture UPN